Syntactic and semantic features of the "Liking" verb group in English and their Vietnamese equivalents / Phan Thị Thùy Ninh; NHDKH Assoc.Prof.Dr Phan Văn Quế - Phan, Thị Thùy Ninh
This present thesis aims at dealing with investigating syntactic and semantic features of the LIKING verb group and their Vietnamese equivalents. The methods selected to analyze the syntactic and semantic features are Descriptive method (to describe liking verb group in terms of their structures and meanings to draw some conclusions on the syntactic and semantic features), and Contrastive method (to detect the similarities and differences in the syntactic and semantic features of liking verb group in English and Vietnamese). The data were collected from five bilingual novels and short stories. From theses novels and short stories, 96 examples are quoted, analyzed and used as the chief source for the qualitative evidence. The received result is that, in terms of syntactic features, this verb group is used in only three sentence patterns (SVO, SVOC, SVOA) among seven sentence patterns; in terms of semantics, the liking verb group can be used with a variety of meaning in Vietnamese. Theoretically, the study will provide a comprehensive and overall knowledge about the syntactic and semantic feature of the LIKING verb group in English. Moreover, the similarities and differences between this verb group in English and In Vietnamese are very helpful in contrasting two languages. Practically, the study will help the Vietnamese learners of English as foreign language use the English LIKING verbs effectively in daily communication.The findings of the study is hopefully to be beneficial to those who are engaged in teaching English as well as those who want to learn English as foreign language.